Evaluation of Labuhanbatu Regency Government Website based on Performance Variables - Armaini, Indah; Dar, Muhammad Halmi; Bangun, Budianto (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Since the establishment of the Labuhanbatu Regency Government website, no efforts have been made to evaluate its performance. This is important to do considering that the Labuhanbatu Regency Government website is a medium of public information needed by the community. The website is also an indicator of the quality assessment of the government as an effort to improve services to the community. This study aims to analyze the website of the Labuhanbatu Regency Government using the evaluation method. The evaluation process is carried out with the help of the GTmetrix measuring tool by measuring website performance through performance metrics such as: First Contentful Paint (FCP), Speed ​​Index (SI), Large Contenful Paint (LCP), Time to Interactive (TTI), Total Blocking Time ( TBT), and Cumulative Layout Shift (CLS). The test results show that the Grade of the website is at level D, with 61% Performance, and 78% Structure. The test results on performance metrics at two test times show a downward trend, where the best FCP is achieved within 2100 milliseconds, SI 6500 milliseconds, LCP 4300 milliseconds, TTI 2100 milliseconds, and TBT 0 milliseconds, although the FCP, SI, and LCP metrics are still in the non-recommended category. The results showed that the GTmetrix measuring instrument could be used to evaluate the website of the Labuhanbatu Regency Government with comprehensive evaluation results. The thing that must be evaluated is the “Reduce initial server response time” aspect which makes the website's initial page load slow. As a solution to these problems, the Labuhanbatu Regency website manager must make improvements to the program code and database queries, implement caching on the server, and perform periodic upgrades to Server hardware, CPU, and Memory.